Análisis Financiero a los Estados Financieros y Programación de la Tesorería de la Empresa Llantera y Servilujos “DENCAR” de la ciudad de Loja - Aguirre Sarango, María Daniela (2023)
The work of Curricular Integration called ANALYSIS TO THE FINANCIAL STATEMENTS AND PROGRAMMING TO THE TREASURY OF THE TIRE AND SERVICE COMPANY "DENCAR", CITY OF LOJA, has been developed with the purpose of evaluating the structure of the financial statements, running the vertical and horizontal analysis in each study period, will also help the company through a treasury programming, which measures in the future if healthy liquidity will be obtained. Fulfilling the first specific objective, the vertical and horizontal analysis was performed, calculating the proportional weight and variations of each of the items that make up the economic and financial structure; it was found that its assets in 2019 have 97,94% and by 2020 97.96%, concentrated on current assets respectively due to the increase in the acquisition of goods; likewise it was evident that of the total liabilities, current liabilities have a higher percentage of participation with 9,69% in 2019 and 10.59% in 2020; in terms of economic structure, expenditure has a share of 89.07% for 2019 and 82.07% for 2020 in the periods analyzed, which means that being high values, does not have a large decrease in its profits, as there is a surplus of merchandise. As for the second objective, it was evident that the company has an average liquidity of $ 9.50 dollars, to cover its short-term debts; with respect to the indicators of activity it was evident that the company does not have accounts receivable, therefore its debts will be dissolved within four to nine months; applying the debt indicators it was known that the company has little capacity to cover its liabilities; The profitability indicators determined the generation of satisfactory returns of approximately 3.00% that compensate for the investment made. The third objective is to present a financial analysis report that includes a synthesis of the results obtained, conclusions and recommendations that serve as a guide to improve the performance of the company. Finally, the programming is made to the treasury, where it is announced that the company will have satisfactory results by 2023.